Economic comparisons of livestock production in communal grazing lands in Zimbabwe - Campbell, Bruce M.; Dore, D.; Luckert, M.; Mukamuri, B.; Gambiza, J. (2000)
During the decade a 'new rangeland science' has emerged. One of the tenets of this science is that pastoralists should not adhere to a single conservative stocking rate but rather, adopt an opportunistic strategy where numbers will fluctuate widely in response to good and bad seasons. It is further argued that opportunistic strategies give higher economic returns compared to strategies based on conservative stocking rates. In this paper the economics of four cattle management scenarios are compared. The analysis is based on a simulation model of the fluctuation over time of animal numbers, outputs and prices, using data from filed surveys and the literature. Results suggest that strategies based on conservative stocking rates would have higher net present values than strategies based on opportunistic stocking rates. Previous analyses have failed to account for losses due to drought and the costs of capital in livestock, and have tended to compare commercial with communal production rather than considering different smallholder production methods. To obtain the full benefits of destocking, however, a decision to destock must be made at the level of the community, as the benefits of improved outputs can only be achieved if the stocking rates of the communal grazing lands are reduced. Collective decisions about managing numbers incur considerable transaction costs, and so the emergence of new institutions is less likely. It is surprising that a tight tracking scenario (where cattle are managed by purchasing and selling to maintain numbers in equilibrium with the available feed resources) is recommended in recent literature as the results of this study suggest that such a system would incur considerable economic losses. The costs of a current programme to reclaim small dams illustrate the environmental costs of the opportunistic scenario. A tight tracking policy is likely to increase environmental degradation and its associated costs. Several serious flaws in papers that elevate opportunistic pastoral systems as giving higher economic returns are identified.